The impact of COVID-19 on municipal food markets: Resilience or innovative attitude? - Nadia Fava; Valentina Rosa Laganà; Agata Nicolosi (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The pandemic has accelerated the search for innovative product/process/service solutions in city markets as well as the search for 'open innovation challenges' more in line with current needs. The aim of the research is to understand the adaptation mechanisms of the local food system and, in particular, of the public space of the market system. The article analyses the change produced by the COVID-19 pandemic in the municipal markets of Sant Feliu de Guixols, Costa Brava, Spain. The data were collected through a semi-structured questionnaire administered to food sellers and contextually to a group of consumers. Factor analysis and the AGIL model were applied to the data collected and were confirmed with cluster analysis. The analysis highlights that the resilience of sellers is no longer sufficient and in many cases, they have equipped themselves with innovative solutions to meet the new customer demands arising from the pandemic (food delivery, e-commerce, take-away food, digital media, etc.). The document concludes with a discussion of food markets and innovations introduced in this period. Further studies can focus on the relationships between food practices and the transformation of urban spaces so that the food market can support new social practices that promote the food transition. The change would represent a switch which would provide traditionally less powerful actors, such as producers, the opportunity to reformulate the food supply chain in a way more linked to the territory. It would also create a resilient dimension for managing other possible food crises and present a challenge to achieving the ultimate goals of the businesses.
Keywords: 650; AGIL model; cluster analysis; consumer survey; COVID-19; factor analysis; municipal food market; open innovation; seller survey